Solar-assisted radiant heating system with nano-B4C enhanced PCM for nearly zero energy buildings - Muhammed Gür; Ezgi Gürgenç; Hakan Coşanay; Hakan F. Öztop (Case Studies in Thermal Engineering)
This investigation centers on the design and performance of a solar-assisted domestic radiator optimized for nearly zero-energy buildings (nZEBs), combining experimental and numerical approaches. The system is powered by a Photovoltaic/Thermal (PV/T) collector, customized to the climatic specifics of Elazığ, Turkey. The study introduces nano-enhanced Phase Change Materials (NEPCM) embedded with Boron Carbide (B4C) nanoparticles to improve efficiency. The NEPCM demonstrating the highest thermal conductivity and specific heat capacity, was selected for numerical analysis. These NEPCM were strategically integrated into the radiator system to maintain ambient room temperatures without additional energy input, particularly during non-solar periods like nighttime. The analysis, conducted under turbulent flow conditions using the finite volume method, reveals that NEPCM significantly improves indoor temperature regulation. The most notable temperature differential, 2.82 K, was observed between configurations with and without PCM. However, the comparison between NEPCM and pure PCM with halved thickness shows a minimal temperature difference of 0.62 K, indicating a slight improvement due to nanoparticle inclusion. These findings highlight both the potential benefits and the limitations of integrating NEPCM into domestic heating systems for sustainable building applications.